Novel reporter alleles of GSK-3α and GSK-3β. - William B Barrell; Heather L Szabo-Rogers; Karen J Liu (PLoS ONE)
Glycogen Synthase Kinase 3 (GSK-3) is a key player in development, physiology and disease. Because of this, GSK-3 inhibitors are increasingly being explored for a variety of applications. In addition most analyses focus on GSK-3β and overlook the closely related protein GSK-3α. Here, we describe novel GSK-3α and GSK-3β mouse alleles that allow us to visualise expression of their respective mRNAs by tracking β-galactosidase activity. We used these new lacZ alleles to compare expression in the palate and cranial sutures and found that there was indeed differential expression. Furthermore, both are loss of function alleles and can be used to generate homozygous mutant mice; in addition, excision of the lacZ cassette from GSK-3α creates a Cre-dependent tissue-specific knockout. As expected, GSK3α mutants were viable, while GSK3β mutants died after birth with a complete cleft palate. We also assessed the GSK-3α mutants for cranial and sternal phenotypes and found that they were essentially normal. Finally, we observed gestational lethality in compound GSK-3β(-/-); GSK3α(+/-) mutants, suggesting that GSK-3 dosage is critical during embryonic development.